KORELASI ANTARA MOTIVASI BELAJAR, PRESTASI BELAJAR, DAN KECERDASAN EMOSIONAL DENGAN PROGRAM TAHFIZUL QUR’AN DI MADRASAH TSANAWIYAH NEGERI 2 PALEMBANG - Deny Priansyah; Muhammad Sirozi; Fajri Ismail (Tadrib: Jurnal Pendidikan Agama Islam, 2021)
The purpose of this research is to find out, describe and analyze; The first is the achievement of Tahfizul Qur'an by 3 madrasah students in Palembang; Second, student achievement of 3 Madrasah participants in Tahfizul Qur'an activities in Palembang; Third, there is a correlation between the achievement of Tahfizul Qur'an and the learning achievement of 3 Madrasah students in Palembang.This research approach uses a quantitative approach with associative research types or correlations between two variables, namely Tahfizul Qur'an as variable X and learning achievement variable Y. The population is 180 students, each in 1 class from the three schools studied, while the sample is 103 people and selected using purposive sampling, the data collection method uses documentation, interviews and observations, while the data analysis technique uses four processes, namely normality testing and hypothesis testing, descriptive analysis using frequency tables, correlation analysis, and regression analysis.The results of the first study, the implementation of the Tahfidz al-Qur'an program at MIN 2, MTs Negeri 2 and MAN 3 Palembang has gone according to plan and has followed the procedures that have been designed by the tahfiz program team in each Madrasa, but have not reached the target, Second, student learning achievement in the three Madrasas is quantitatively (cognitive) quite good, with an average value of 77.7 to 80.74. Third, student achievement in the field of tahfidzul qur'an is quantitatively very good, with an average score between 77, 71 to 90.33. Fourth, there is a positive relationship with moderate intensity between the achievement of tahfidz Qur'an and student learning achievement, with a correlation number of 0.439.